Prevalence, Sociodemographic, and Clinical Correlates of Older Chinese Patients With Deficit Schizophrenia. (November 2019) - Liu, Junjun; He, Jinfeng; Cheng, Min; Cao, Hui; Zhang, Xiangrong
Objective: No study has investigated the frequency and risk factors for deficit schizophrenia (DS) in Chinese Han population. We investigated the prevalence of DS among community-dwelling older Chinese patients with schizophrenia and examined the sociodemographic and clinical correlates of DS in this population. Methods: A total of 326 community-dwelling older patients with schizophrenia were recruited in this cross-sectional study. Deficit schizophrenia was confirmed using the Chinese version of the Schedule for the Deficit Syndrome. Data pertaining to sociodemographic and clinical characteristics were collected. Psychopathology was assessed using the Positive and Negative Syndrome Scale (PANSS). Results: The prevalence of DS in the study population was 26.7% (31.2% among male patients and 21.6% among female patients with schizophrenia). Patients with DS had significantly higher current smoking rate, hospitalizations, PANSS negative score, PANSS total score, and had earlier age at onset than patients with non-deficit schizophrenia (N-DS). The N-DS patients had higher PANSS positive scores and a greater proportion of married patients. Multiple logistic regression analysis indicated that negative PANSS score (odds ratio [OR] = 1.10, 95% confidence interval [CI] = 1.04-1.16, P < .001), male sex (OR = 1.71, 95% CI = 1.53-1.91, P = .037), age at onset (OR = 0.88, 95% CI = 0.82-0.94, P = .035), and current smoking (OR = 1.37, 95% CI = 1.15-1.63, P = .041) were independently associated with DS. Conclusion: Deficit schizophrenia is relatively common among older community-dwelling Chinese patients with schizophrenia. High negative symptom scores, male sex, early onset, and smoking were independent correlates for DS.